2009
DOI: 10.1111/j.1476-5381.2008.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid inhibits voltage‐gated sodium channels and invasiveness in prostate cancer cells

Abstract: Background and purpose:The voltage-gated Na + channels (Nav) and their corresponding current (INa) are involved in several cellular processes, crucial to metastasis of cancer cells. We investigated the effects of eicosapentaenoic (EPA), an omega-3 polyunsaturated fatty acid, on INa and metastatic functions (cell proliferation, endocytosis and invasion) in human and rat prostate cancer cell lines (PC-3 and Mat-LyLu cells). Experimental approach: The whole-cell voltage clamp technique and conventional/quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 48 publications
2
38
1
Order By: Relevance
“…5E). Like NSCLC, metastatic prostate cancer is also associated with functional expression of Na v 1.7 (Diss et al, 2001;Diss et al, 2005;Nakajima et al, 2009;Yildirim et al, 2012). Together, these data support a role for Na v 1.7 in the development of an invasive cancer phenotype in vivo.…”
Section: Na V 17 Expression Is Enhanced In Cancerous Lung Tissuesupporting
confidence: 59%
See 1 more Smart Citation
“…5E). Like NSCLC, metastatic prostate cancer is also associated with functional expression of Na v 1.7 (Diss et al, 2001;Diss et al, 2005;Nakajima et al, 2009;Yildirim et al, 2012). Together, these data support a role for Na v 1.7 in the development of an invasive cancer phenotype in vivo.…”
Section: Na V 17 Expression Is Enhanced In Cancerous Lung Tissuesupporting
confidence: 59%
“…Voltage-gated Na + channels (Na v ), normally associated with cellular excitability, have been found to play crucial roles in metastatic behaviours of several cancers, including breast Fraser et al, 2005;Gao et al, 2009;Gillet et al, 2009;Roger et al, 2003), prostate (Abdul and Hoosein, 2002;Bennett et al, 2004;Diss et al, 2001;Diss et al, 2005;Grimes et al, 1995;Laniado et al, 1997;Nakajima et al, 2009;Smith et al, 1998), cervical (Diaz et al, 2007), colon (House et al, 2010), ovarian (Gao et al, 2010), SCLC (Blandino et al, 1995;Onganer and Djamgoz, 2005;Onganer et al, 2005;Pancrazio et al, 1989) and NSCLC (Roger et al, 2007). In prostate cancer, functional expression of Na v enhances cellular migration, invasion and endocytosis (Ding et al, 2008;UysalOnganer and Djamgoz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that LNCaP cell growth was inhibited by EPA and DHA (8). The effect of EPA and DHA on the proliferation and invasion of the breast cancer cell lines MDA-MB-231 and MDA-231 Luc and the effect of EPA and DHA on breast cancer metastasis to bone following intracardiac injection of MDA-MB-231 and MDA-231-Luc cells was also evaluated in other studies (9,10). In brief, MDA-MB-231 cells were injected into mice that were fed experimental diets containing EPA or DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that functional VGSC expression occurs in a variety of carcinomas and promotes metastatic behaviour. Such carcinomas include BCa as well as cancers of the prostate (Grimes et al 1995;Laniado et al 1997;Nakajima et al 2009), lung (Onganer and Djamgoz 2005;Campbell et al 2013), colon (House et al 2010) and cervix (Diaz et al 2007). It has been suggested, therefore, (1) that VGSC up-regulation is an early event in metastatic progression and (2) that VGSC expression is a 'switch,' necessary and sufficient for engaging cancer cells in a highly invasive state.…”
mentioning
confidence: 99%